PENGEMBANGAN SOAL PENGAYAAN MODEL PISA LEVEL 4 KELAS VII SMP - Tria Gustiningsi (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2016)
This study aims to develop enrichment problems using PISA which valid and practical. Beside that, this study aims to know potential effects of problems which develop. The researchers use design research using the type of development study to reach the objective of this study. This study consists of two stages, which are preliminary and prototyping (formative evaluation) stages. The preliminary stage, researchers conducted several activities that analyzing the students that will be the subject, analyzing curriculum, and analyzing the PISA problems which developed. The prototyping stage consists of self-evaluation, expert reviews, one-to-one experiments, small group experiment, and field test. The problems were tested to 12 seventh graders in SMPN 1 Palembang, Indonesia. The data were collected by walk-through, test, interviews, and field notes. The result of this study is the enrichment problems using PISA which develop are valid and practical. Potential effects of those problems are reasoning ability, representationability, communication skills, and mathematical ability